ANALISIS STRUKTURAL MATERI FIQIH BAB SHALAT DI KITAB SAFINATUN NAJAH - Ahmad Muchyidin Asad; Ach Faisol; Qurroti Ayun (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Fiqh is the result of ijtihad achieved by a fiqh expert in an attempt to find the law of Allah SWT. Fiqh is an interpretation of Sharia law. The purpose of this study was to find out the perfect way of praying according to the Safinatun Najah book, to find out the concepts presented by Sheikh Salim bin Sumair in the Safinatun Najah book, and to find out the supporting materials that explain the Safinatun Najah book. This research is categorized in the type of library research (library research). In analyzing the data, after the data is collected, the method used by the author to analyze the data that has been obtained is the method of